Optimering av intern logistik - Bladh, Johannes; Sönegård, Johan (My University, 2015)
A company is working to make the production line more efficient, which will be accomplished with redistribution of resources and implementation of higher level of automation and work routines. The company will, in the future, rearrange work tasks between storage and assembly personnel where the assembly does not get components themselves, it will be brought to them. Today the storage personnel feed two out of the seven assembly stations and for them to be able to take on all stations a new system must be applied. How this system will be created and what is needed to be done will be analyzed in this report. After observations, interviews and collecting of data of the current situation between storage and assembly, including the companies vision of the future, has a situation analysis been made and will be the basis of what is needed to be improved. The report will be a base for upcoming improvements within the company and will therefore not contain any direct results but solutions and recommendations which are based on the literature on the subject and a benchmark. After studies and observations it was clear that the storage location should be centralized instead of the current system with shelves at every assembly station. This is to simplify the logistics and shorten the distance of transportation for the milkrounds. A new and more efficient computer system should be acquired that can handle more data and the use of barcode readers for the storage personnel. This system should also be created as flexible as possible for easy implementation of future automation in inventory and assembly. For the continuation of working with Lean in the production unit loads should be applied to get the storage more correct and new work routines needs to be developed to make sure that the weight control of incoming components is correctly done. Focus has been given to inventory and assembly. Production, receipt, planning and final storage are all vital departments who works directly with storage and assembly, but because of the timeframe only a summary was done of their flow of information and significance, what is being sent and received.
Keywords: Produktion; Produktionsteknik; Production; Manufacturing engineering